Denitrifier Still Has the Important Role in Nitrate Reduction to N2 Although It is Not the Predominant Population in the Estuarine Bacterial Community of Nitrate Reducing Bacteria - Rusmana, Iman; Nedwell, David B. (HAYATI Journal of Biosciences, 2024)
Denitrification and nitrate-ammonification are the responsible processes for nitrate removal in the estuaries. Temperature, nitrate and organic carbon availability are key factors controlling a rate of the nitrate reduction processes. This mixed cultures chemostat study investigates the competition ability and their nitrate reduction end-products of the bacteria isolated from an estuary at different temperatures. This study will help us to understand the seasonal nitrate reduction processes in an estuary. The experiments showed that a nitrate-ammonifier was the predominant process in the steady-state chemostat at high temperature. While a facultative denitrifier-nitrate ammonifier was the predominant process at low temperature. However, the main end products of nitrate reduction at high temperature were up to 61% N2 indicating a denitrifier still had an important role in the end products of nitrate reduction in the estuary. The data also showed that a nitrite respiring bacterium reduced nitrite to N2, that responsible for approximately 6-9% of total N2 produced in the culture. This study confirmed that nitrate ammonifiers out-compete denitrifiers at high temperature, however, denitrifiers still had an important role in end products of nitrate reduction.